Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6cp00520a
|View full text |Cite
|
Sign up to set email alerts
|

Force exerted by a nanoscale capillary water bridge between two planar substrates

Abstract: Molecular dynamics simulation of a nanoscale capillary water bridge between two planar substrates is used to determine the resulting force between the substrates without arbitrariness regarding geometry and location of the free surface of the bridge. The substrates are moderately hydrophilic. The force changes continuously as the separation between the substrates changes except for small gaps where it becomes discontinuous because the bridge is unable to adopt stable configurations at any distance apart. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…Based on the ATR-IR spectroscopy study, Asay et al reported that the full coverage of monolayer adsorption occurs at RH < 10% . The silicon oxide surface is fully covered with the adsorbed water molecules, even at the lowest RH condition measured in this study (10%).…”
Section: Resultsmentioning
confidence: 50%
See 4 more Smart Citations
“…Based on the ATR-IR spectroscopy study, Asay et al reported that the full coverage of monolayer adsorption occurs at RH < 10% . The silicon oxide surface is fully covered with the adsorbed water molecules, even at the lowest RH condition measured in this study (10%).…”
Section: Resultsmentioning
confidence: 50%
“…The lower wavernumber component can be attributed to the strongly hydrogen-bonded solidlike network and the higher wavenumber component is characteristic of the weakly hydrogen-bonded liquidlike structure. The fact that the spectrum at 30% RH is dominated by the lower wavenumber component means that the thin water layer adsorbed on SiO x surface assumes the solidlike structure with stronger hydrogen bond interactions under this condition. As RH increases above 50%, the adsorbed water layer becomes thicker and the liquidlike structure becomes dominant. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations